Improvement model to increase efficiency through the use of 5S, TPM and SMED tools in a plastic SME company (LACCEI, 2024)
Over time, the manufacturing industry has evolved enormously, requiring increasingly efficient processes, with reduced repair times and fewer defects. In this sense, in the case study a low efficiency in the production process was identified, given that the percentage in the plastics sector is 73%. Therefore, a more detailed analysis was carried out and it was found that high repair time and reprocessing due to defects are the main causes. Consequently, an improvement model based on 5S, TPM and SMED tools is proposed with the objective of reducing the costs of the described problem, which are equivalent to 7.45% of revenues. In addition, it seeks to reduce reprocesses due to defects by 43%, while repair time is reduced by 77%. Applying the presented model, it was obtained a decrease of the presented 5S deficiencies by 11.50%, increase of efficiency to 73.65%, improvement of machine availability to 85.46% and reduction by 1.36% and up to 39.24 of the effects of burn marks and setup time, respectively. Thus, it is expected that companies belonging to the plastics or related sectors will use the results obtained as a reference for improvement.